THE CHALLENGES FOR EDUCATION INSTITUTIONS IN THE INCLUSION OF STUDENTS WITH LANGUAGE AND LEARNING DISABILITIES - Ustinova, Kristīne (Education Reform: Education Content Research and Implementation Problems, 2024)
Living in an era of transformation, changes in the educational system are inevitable. Schools are an educational, cultural and social environment that needs to be high quality, modern and inclusive. A positive experience within the process of inclusion is important not only for pupils entering a comprehensive school, but also for their parents, current pupils and teaching staff of all fields. Included pupils are pupils with language and learning disabilities who need an individual approach, a well-thought-out learning strategy, support and an understanding attitude. The aim of this paper is to theoretically identify the challenges that teachers face in the process of inclusion of pupils with language and learning disabilities. The paper analyses the theory of inclusive education, addresses the aspect of support provision for pupils and draws conclusions. Schools have been entrusted with the nationally important task of creating a cohesive, supportive and nurturing learning environment and compassionate and understanding relationships that help people grow up to be self-confident and ambitious. Only time will allow us to assess whether it was the right strategic decision to include all pupils with language and learning disabilities in comprehensive schools. Despite the challenges of special education transformation, schools have a vision for development and the will to work.